The influence of birth site on short-term outcomes of encephalopathic newborn infants treated with therapeutic hypothermia at Groote Schuur Hospital, Cape Town, South Africa - Nakibuuka, Victoria (Department of Paediatrics and Child Health, 2015)
Background: International consensus guidelines recommend that term or near-term newborns with moderate or severe hypoxic ischaemic encephalopathy (HIE) should be treated with induced hypothermia within 6 hours of birth, but many of the affected babies are born outside treatment centers. There are conflicting data describing the influence of birth site on outcome after HIE - and no published data from South Africa. Objective: To compare the frequency of abnormal outcome (mortality or abnormal aEEG) before discharge between inborn and outborn infants treated with hypothermia Methods: This was a retrospective analysis of data extracted from a prospectively collated registry of babies with moderate or severe HIE, treated with hypothermia in a tertiary hospital in South Africa, between 1 January 2011 and 31 December 2012. Results: A total of 57 babies were treated with hypothermia of which 23 (40%) were inborn and 34 (60%) outborn. Cooling was initiated earlier among the inborn babies (age 2.3 hours vs. 4.3 hours, p=0.002). Pregnancy complications and abnormal intrapartum fetal heart rates occurred more frequently in inborn infants (65.2 % vs. 24.2 %, p=0.0001 and 47.8% vs. 20.6%, p =0.03 respectively). More outborn babies died or had an abnormal aEEG at 48 hours (32 % vs. 22 %, p=0.556) and fewer outborn babies achieved normal feeding at discharge (22% vs. 38%, p = 0.189), but these differences were not statistically significant. Conclusion: The majority of infants treated with induced hypothermia in an urban/peri-urban setting in South Africa were not born in a cooling centre. There were significant delays in initiating cooling among the outborn babies. Short-term morbidity and mortality were not significantly different in outborn babies but interpretation is limited by the small sample size.